Recent advances in the implant-based drug delivery in otorhinolaryngology. (May 2020) - Tan, Fei; Zhu, Yunqing; Ma, Zhaoxin; Al-Rubeai, Mohamed
Abstract: The surgical implant is an interdisciplinary therapeutic modality that offers unique advantages in the daily practice of otorhinolaryngology. Some well-known examples include cochlear implants, bone-anchored hearing aids, sinus stents, and tracheostomy tubes. Neuroprotective, osteogenic, anti-inflammatory, and antimicrobial effects are among their established or pursued functions. Implant-based drug delivery affords an efficient and potent approach to enhancing these therapeutic functions. Recent innovations have infiltrated all four elements of a drug-eluting implant. The purpose of this pre-clinical, biotechnology-oriented review is to discuss these developments in terms of the implant biomaterial, loaded medication, delivery pattern, and system fabrication. Cell-mediated neurotrophin release, fabrication of a hydroxyapatite-supported system, biodegradable polymer-based implants, and multiclass and multidrug delivery are some representative advancements. The ultimate goal here is to bridge the gap between biotechnology advances and clinical needs. The review is concluded with a perspective regarding the future opportunities and challenges in this popular and rapidly developing subject of research. Statement of Significance: Surgical implants and local drug delivery are representative modern modalities of surgical treatment and medical treatment, respectively. Their synergy offers unique therapeutic advantages, such as minimal systemic side effects, proximity-related high efficiency, and potential absorbability. The applications of implant-based drug delivery have infiltrated otorhinolaryngology and head & neck surgery, which is well known for its related tissue diversity and surgical complexity. Examples discussed here include cochlear implants, bone-anchored hearing aids, sinus stents, and airway tubes. This timely review focuses primarily on the four fundamental components of an implant-based drug delivery system, namely implant biomaterial, loaded medication, delivery pattern, and system fabrication. A particular emphasis is placed upon the in vitro cellular and in vivo animal studies that demonstrate pre-clinical potentials. Graphical abstract: Image, graphical abstract